Composite current collector and its manufacturing method, electrode piece and secondary battery
By adopting composite current collectors with different aluminum particle size distributions in non-aqueous secondary batteries, the problems of low surface energy and high interface resistance of the existing current collectors are solved, and the effect of improving battery capacity and cycling performance is achieved.
Patent Information
- Application Number
- JP2024562215
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-25
- Filing Date
- 2022-05-27
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2042-05-27
AI Technical Summary
The positive electrode electrolyte current collector of the existing non-aqueous secondary batteries is difficult to effectively adsorb active substances due to low surface energy, resulting in excessive interface resistance and affecting battery performance.
Using a composite current collector composed of a polymer base film and a double-layer aluminum plating layer, the first sub-layer and the second sub-layer of the aluminum plating layer have different particle size distributions, the aluminum particle size of the first sub-layer is between 10 nm and 30 nm, and the aluminum particle size of the second sub-layer is between 80 nm and 100 nm.
By controlling the distribution of aluminum particle sizes of different sub-layers, the surface energy and conductivity of the composite current collector are improved, the interface resistance is reduced, and the capacity and circulation performance of lithium-ion batteries are improved.
Smart Images

Figure 2025513924000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of batteries, and in particular to a composite current collector and its manufacturing method, an electrode strip and a secondary battery. [Background technology]
[0002] The positive electrode current collector of a general non-aqueous secondary battery is manufactured by a rolling process using high-purity aluminum foil. In order to ensure the flatness of the aluminum foil, the surface of the press roll used in the rolling process is very smooth, which results in a low surface energy of the current collector. When the positive electrode active material is applied to the current collector, the active material cannot be effectively attached to the current collector, and the interface resistance between the active material and the current collector is too large, which affects the performance of the battery. Summary of the Invention [Problem to be solved by the invention]
[0003] Therefore, it is necessary to provide a composite current collector that can increase the surface energy of the current collector and reduce the interface resistance between the current collector and the active material.
[0004] There is also a need to provide a method for making the composite current collector, and electrode strips and secondary batteries that include the composite current collector. [Means for solving the problem]
[0005] A composite current collector comprising a polymer-based film and an aluminum plating layer provided on both surfaces of the polymer-based film, the aluminum plating layer comprising a first sublayer and a second sublayer, the first sublayer being closer to the polymer-based film than the second sublayer, the aluminum particles in the first sublayer having a particle size of 10 nm to 30 nm, and the aluminum particles in the second sublayer having a particle size of 80 nm to 100 nm.
[0006] In one embodiment therein, the thickness of each of the aluminum plating layers is independently 0.3 μm to 3 μm.
[0007] In one embodiment, the first sublayer is a plurality of first sublayers, which are sequentially stacked and arranged between the polymer-based film and the second sublayer.
[0008] In one embodiment thereof, the number of the first sub-layers is 19 or less.
[0009] In one embodiment thereof, the thickness of the polymer-based film is 1 μm to 25 μm.
[0010] In one embodiment thereof, the polymer-based film is at least one selected from the group consisting of polyethylene, polypropylene, polymethylpentene, and polyethylene terephthalate.
[0011] A method for producing a composite current collector, the method including the step of producing a composite current collector by forming an aluminum plating layer on both surfaces of a polymer-based film, the aluminum plating layer including a first sublayer and a second sublayer, the first sublayer being closer to the polymer-based film than the second sublayer, the aluminum particles in the first sublayer having a particle size of 10 nm to 30 nm, and the aluminum particles in the second sublayer having a particle size of 80 nm to 100 nm.
[0012] In one embodiment, the aluminum plating layer is formed by vacuum deposition or magnetron sputtering.
[0013] In one embodiment thereof, in the process of forming the aluminum plating layer, the process parameters are: evaporation temperature not less than 600°C; vacuum degree not more than 0.01 Pa; plating speed not less than 10 m / min; and the evaporation temperature for forming the first sub-layer is higher than the evaporation temperature for forming the second sub-layer.
[0014] The evaporation temperature for forming the first sub-layer is 700°C to 750°C, and the evaporation temperature for forming the second sub-layer is 600°C to 700°C.
[0015] The electrode piece includes a current collector, which may be a composite current collector as described above or a composite current collector made by the method for making a composite current collector as described above, and an active material coated on both sides of the current collector.
[0016] A secondary battery includes the electrode piece described above. Effect of the Invention
[0017] The composite current collector includes a polymer-based film and an aluminum plating layer. The polymer-based film is used to support the aluminum plating layer. The aluminum plating layer includes a structure of two layers with different particle sizes. The aluminum particles in the first sublayer have a small particle size and high density, so that the aluminum plating layer has a high electrical conductivity. The aluminum particles in the second sublayer have a large particle size and low density, so that the surface energy of the aluminum plating layer is high and the problem of high interface resistance of the conventional aluminum foil is well solved. Therefore, the composite current collector can ensure high surface energy and high electrical conductivity by controlling the particle size of the particles in different sublayers of the aluminum plating layer, and can obviously improve the interface internal resistance between the battery pole piece and the current collector during the coating process of the active material, and improve the capacity and cycle performance of the lithium battery. [Brief description of the drawings]
[0018] [Figure 1] FIG. 2 is a structural schematic diagram of a composite current collector according to one embodiment. [Diagram 2] FIG. 2 is a comparison diagram of the internal resistance of lithium batteries manufactured using the composite current collectors in Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] In the following, in order to facilitate understanding of the present invention, the present invention will be described more completely in conjunction with specific embodiments. In the specific embodiments, preferred examples of the present invention are provided. However, the present invention can be realized in many different forms and is not limited to the examples described herein. On the contrary, the purpose of providing these examples is to make the disclosure of the present invention more complete and comprehensive.
[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention pertains. The terms used in the present specification are merely for describing specific examples and are not intended to limit the present invention.
[0021] In this specification, the particle size of aluminum particles refers to the median diameter.
[0022] Referring to FIG. 1, a composite current collector 100 in one embodiment includes a polymer-based film 110 and an aluminum plating layer 120 provided on both surfaces of the polymer-based film 110, the aluminum plating layer 120 including a first sublayer 122 and a second sublayer 124, the first sublayer 122 being closer to the polymer-based film 110 than the second sublayer 124, the particle size of the aluminum particles in the first sublayer 122 being 10 nm to 30 nm, and the particle size of the aluminum particles in the second sublayer 124 being 80 nm to 100 nm.
[0023] Specifically, the particle size of the aluminum particles in the first sub-layer 122 is 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 10 nm to 15 nm, 15 nm to 20 nm, 10 nm to 20 nm, 15 nm to 25 nm, 20 nm to 25 nm, or 25 nm to 30 nm, etc. The particle size of the aluminum particles in the second sub-layer 124 is 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, 80 nm to 85 nm, 85 nm to 90 nm, 90 nm to 95 nm, 95 nm to 100 nm, 80 nm to 90 nm, or 85 nm to 95 nm.
[0024] Further, there are a plurality of first sublayers 122, and the plurality of first sublayers 122 are sequentially stacked and arranged between the polymer-based film 110 and the second sublayer 124. Further, the number of the first sublayers 122 is 19 or less. For example, the number of the first sublayers 122 is 2, 5, 8, 10, 12, 15, 17, or 19. Preferably, the number of the first sublayers 122 is 8 to 12.
[0025] Wherein, the thickness of each aluminum plating layer 120 is 5 μm or less. Furthermore, the thickness of each aluminum plating layer 120 is independently 0.3 μm to 3 μm. For example, the thickness of each aluminum plating layer 120 is independently 0.3 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 0.3 μm to 0.5 μm, 0.5 μm to 1 μm, 1 μm to 1.5 μm, 1.5 μm to 2 μm, 2 μm to 2.5 μm, 2.5 μm to 3 μm, 0.3 μm to 1 μm, 0.5 μm to 1.5 μm, 1 μm to 2 μm, 1.5 μm to 2.5 μm, 2 μm to 3 μm, etc. Furthermore, the aluminum plating layers 120 are provided symmetrically on both surfaces of the polymer-based film 110.
[0026] The aluminum particles in the first sub-layer 122 have a small particle size and high density, which ensures high electrical conductivity of the aluminum plating layer 120. In addition, the aluminum particles in the second sub-layer 124 have a large particle size and low density, which solves the problem that the surface energy of the outermost layer of the aluminum plating layer 120 is high and that the interface resistance of conventional aluminum foils is high.
[0027] Furthermore, the purity of the aluminum plating layer 120 is 99.8% or more.
[0028] Specifically, the thickness of the polymer-based film 110 is 1 μm to 25 μm. For example, the thickness of the polymer-based film 110 is 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 1 μm to 10 μm, 5 μm to 15 μm, 10 μm to 20 μm, 1 μm to 5 μm, 5 μm to 10 μm, 10 μm to 15 μm, 15 μm to 20 μm, 20 μm to 25 μm, etc.
[0029] Specifically, the polymer-based film 110 is at least one selected from the group consisting of polyethylene, polypropylene, polymethylpentene, and polyethylene terephthalate. Since the density of the polymer-based film 110 is low, the density of the composite current collector 100 can be further reduced, and the energy density of the lithium-ion battery can be improved.
[0030] In one embodiment therein, the peel force between the aluminum plating layer 120 and the polymer-based film 110 is greater than or equal to 2 N / m.
[0031] Specifically, the thickness of the composite current collector 100 is 3 μm to 30 μm. For example, the thickness of the composite current collector 100 is 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 3 μm to 5 μm, 5 μm to 10 μm, 10 μm to 15 μm, 15 μm to 20 μm, 25 μm to 30 μm, 3 μm to 10 μm, 5 μm to 15 μm, 10 μm to 20 μm, 15 μm to 25 μm, or 20 μm to 30 μm. Preferably, the thickness of the composite current collector 100 is 3 μm to 16 μm.
[0032] Furthermore, in this embodiment, the composite current collector 100 is a positive electrode current collector.
[0033] The conventional positive electrode current collector is an aluminum foil, which is produced by a rolling process. The specific steps are as follows:
[0034] a. The electrolytic aluminum melt is fed into a smelting furnace, and 20% to 40% of the total weight of the electrolytic aluminum melt is added as an aluminum ingot. The temperature of the melt is controlled to 750°C to 780°C, and the mass percentage of each element component in the melt is adjusted to be Si: 0.1% to 0.15%, Fe: 0.45% to 0.5%, Cu: 0.1% to 0.15%, Mn: 1.1% to 1.2%, Ti: 0.02% to 0.04%, and the balance is Al. The melt is refined by spraying a refining agent with pure nitrogen gas or pure argon gas, and is thoroughly and uniformly stirred, and the refining time is 8 to 10 minutes. After that, it is left to stand for 15 to 25 minutes, and the dross on the surface of the aluminum liquid is removed, and then it is put into a static furnace, and the temperature in the static furnace is controlled to 750°C to 760°C. The aluminum liquid in the static furnace is sent to a trough, and aluminum titanium boron thread is added in the opposite direction to refine the crystal grains. After that, the aluminum liquid is degassed in a degassing box with pure nitrogen gas or pure argon gas. After degassing, the aluminum liquid is filtered and purified with a ceramic foam filter sheet. The purified aluminum liquid is sent to a rolling mill and rolled to produce billets with a thickness of 5.0 mm to 10.0 mm.
[0035] b. The billet obtained in step a is cold-rolled to a thickness of 3.0 mm to 5.0 mm, and then homogenized annealing is performed. The homogenization annealing temperature is 440° C. to 490° C., and the annealing time is 20 hours to 30 hours.
[0036] c. The homogenized annealed billet is cold-rolled to a thickness of 0.2 mm to 0.6 mm, and then recrystallization annealing is performed. The recrystallization annealing temperature is 270°C to 330°C, and the annealing time is 12 hours to 19 hours.
[0037] d. The recrystallized annealed billet is then rolled to the required thickness for the anode aluminum foil.
[0038] The surface energy of the current collector prepared by the above-mentioned conventional method is low, so that when the positive electrode active material is applied to the current collector, the active material cannot effectively adhere to the current collector, and the interface resistance between the active material and the current collector is too large, which affects the performance of the battery.
[0039] The composite current collector in this embodiment includes a polymer-based film and an aluminum plating layer. The polymer-based film is used to support the aluminum plating layer. The aluminum plating layer includes a structure of two layers with different particle sizes. The aluminum particles in the first sublayer have a small particle size and high density, so that the aluminum plating layer can have a high electrical conductivity. The aluminum particles in the second sublayer have a large particle size and low density, so that the surface energy of the outermost layer of the aluminum plating layer is high, and the problem of high interface resistance of the conventional aluminum foil can be well solved. Therefore, the composite current collector not only has high electrical conductivity, but also has high surface energy, and can obviously improve the interface internal resistance between the battery pole piece and the current collector during the coating process of the active material, and improve the capacity and cycle performance of the lithium battery.
[0040] In addition, since aluminum foil manufactured by a conventional rolling process is limited by the process, it is difficult to make the aluminum foil thin. However, in this embodiment, the polymer base film and the aluminum plating layer are combined, so that the thickness of the composite current collector can be reduced.
[0041] Specifically, in this embodiment, the surface energy of the surface layer of the composite current collector is more than 65 dynes / cm, and the conductivity of the aluminum plating layer on one side is 3.7×10 6 The composite current collector has a pin puncture strength of 50 gf or more, an MD stretch strength of 150 MPa or more, a TD stretch strength of 150 MPa or more, an MD elongation of 10% or more, and a TD elongation of 10% or more. Therefore, the composite current collector ensures electrical conductivity, improves surface energy, and has good strength and elongation, and can be applied to batteries in place of conventional aluminum foil.
[0042] In one embodiment, a method for making a composite current collector includes the following steps.
[0043] An aluminum plating layer is formed on each side of the polymer-based film to produce a composite current collector.
[0044] The aluminum plating layer includes a first sublayer and a second sublayer, the first sublayer is closer to the polymer-based film than the second sublayer, the aluminum particles in the first sublayer have a particle size of 10 nm to 30 nm, and the aluminum particles in the second sublayer have a particle size of 80 nm to 100 nm.
[0045] Specifically, the aluminum plating layer is formed by vacuum deposition or magnetron sputtering. Furthermore, the aluminum plating layer is formed using a high-purity aluminum ingot (with a purity of 99.8% or more) as a raw material.
[0046] In one embodiment, in the process of forming the aluminum plating layer, the process parameters are: evaporation temperature is 600° C. or higher, vacuum degree is less than 0.01 Pa, deposition temperature is more than 10 m / min, and the vacuum degree is 0.002 Pa to 0.005 Pa, and deposition speed is 80 m / min to 120 m / min.
[0047] Furthermore, the evaporation temperature in the process of forming the first sub-layer is higher than the evaporation temperature in the process of forming the second sub-layer. By controlling the temperature in the process of forming the first sub-layer and the second sub-layer, the particle size of the aluminum particles in the first sub-layer and the second sub-layer is controlled. Furthermore, the evaporation temperature in the process of forming the first sub-layer is 700°C to 750°C, and the evaporation temperature in the process of forming the second sub-layer is 600°C to 700°C.
[0048] In some embodiments, the first sublayer is multiple, and the multiple first sublayers are sequentially stacked and arranged between the polymer-based membrane and the second sublayer. Furthermore, the number of first sublayers is 19 or less. For example, the number of first sublayers is 2, 5, 8, 10, 12, 15, 17, or 19. Preferably, the number of first sublayers is 8 to 12.
[0049] Specifically, the thickness of each aluminum plating layer is 5 μm or less. Furthermore, the thickness of each aluminum plating layer is independently 0.3 μm to 3 μm. For example, the thickness of each aluminum plating layer is independently 0.3 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 0.3 μm to 0.5 μm, 0.5 μm to 1 μm, 1 μm to 1.5 μm, 1.5 μm to 2 μm, 2 μm to 2.5 μm, 2.5 μm to 3 μm, 0.3 μm to 1 μm, 0.5 μm to 1.5 μm, 1 μm to 2 μm, 1.5 μm to 2.5 μm, 2 μm to 3 μm, etc. Furthermore, the aluminum plating layers are provided symmetrically on both surfaces of the polymer-based film 110.
[0050] Specifically, the thickness of the polymer-based film is 1 μm to 25 μm. For example, the thickness of the polymer-based film is 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 1 μm to 10 μm, 5 μm to 15 μm, 10 μm to 20 μm, 1 μm to 5 μm, 5 μm to 10 μm, 10 μm to 15 μm, 15 μm to 20 μm, 20 μm to 25 μm, etc.
[0051] Specifically, the polymer-based film is at least one selected from polyethylene, polypropylene, polymethylpentene, and polyethylene terephthalate. Since the density of the polymer-based film is low, the density of the composite current collector 100 can be further reduced, and the energy density of the lithium-ion battery can be improved.
[0052] In one embodiment therein, the peel force between the aluminum plating layer and the polymer-based film is greater than or equal to 2 N / m.
[0053] Specifically, the thickness of the composite current collector is 3 μm to 30 μm. For example, the thickness of the composite current collector is 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 3 μm to 5 μm, 5 μm to 10 μm, 10 μm to 15 μm, 15 μm to 20 μm, 25 μm to 30 μm, 3 μm to 10 μm, 5 μm to 15 μm, 10 μm to 20 μm, 15 μm to 25 μm, or 20 μm to 30 μm. Preferably, the thickness of the composite current collector is 3 μm to 16 μm.
[0054] Furthermore, in this embodiment, the composite current collector is a positive electrode current collector.
[0055] Furthermore, the polymer-based film is unwound under an unwinding tension of 5N to 30N. The method further includes a winding step after forming the aluminum plating layer. The winding tension is 5N to 25N.
[0056] The manufacturing method of the composite current collector is simple, and the aluminum plating layer includes a bilayer structure with different particle sizes through multiple deposition. The aluminum particles in the first sublayer have a small particle size and high density, so that the aluminum plating layer has a high electrical conductivity, and the aluminum particles in the second sublayer have a large particle size and low density, so that the surface energy of the aluminum plating layer is high, and the problem of high interface resistance of the conventional aluminum foil is well solved. Therefore, the composite current collector prepared by the above method not only has high electrical conductivity, but also has high surface energy, and can obviously improve the interface internal resistance between the battery pole piece and the current collector during the coating process of the active material, and improve the capacity and cycle performance of the lithium battery.
[0057] The electrode piece according to one embodiment includes a current collector, which is the composite current collector according to the above embodiment, and an active material coated on both sides of the current collector. The electrode piece is a positive electrode piece. The active material may be a positive electrode active material commonly used in the art, and will not be described again here.
[0058] A secondary battery according to an embodiment includes the above-mentioned electrode piece. Specifically, the electrode piece is a positive electrode piece. The secondary battery further includes a negative electrode piece, a separator, and an electrolyte. The specific negative electrode piece, separator, and electrolyte may be those commonly used in the art, and will not be described here again.
[0059] In one embodiment, the secondary battery is a non-aqueous secondary battery, such as a lithium battery, which has low interfacial internal resistance, high capacity, and excellent cycle performance.
[0060] The following is a specific example part.
[0061] Example 1 In this embodiment, a composite current collector having a thickness of 8 micrometers is provided, which includes a polymer-based film PET having a thickness of 6 micrometers and an aluminum plating layer symmetrically provided on both sides of the polymer-based film, and the aluminum plating layer on one side has a thickness of 1 micrometer. The manufacturing process is specifically as follows:
[0062] (1) A polymer-based film PET with a thickness of 6 micrometers and a high-purity aluminum ingot with a purity of 99.9% were selected.
[0063] (2) The polymer-based film and a high-purity aluminum ingot were each placed in a vacuum deposition apparatus.
[0064] (3) The high-purity aluminum ingot is plated with aluminum on the upper and lower surfaces of the polymer-based film by a vacuum deposition device to obtain an aluminum plating layer. The unwinding tension of the polymer-based film is 8N. The aluminum plating layer on one side needs to be evaporated 16 times. The first 15 evaporations are used to obtain 15 first sublayers, each of which has an aluminum particle diameter of 20nm, and the 16th evaporation is used to obtain a second sublayer, each of which has an aluminum particle diameter of 85nm. The process parameters for the evaporation process are a vacuum degree of 5×10 -2The evaporation temperature for the first 15 times was 700℃, and the evaporation temperature for the 16th time was 620℃.
[0065] (4) After the deposition was completed, a winding operation was carried out with a winding tension of 6 N to obtain the composite current collector of this example.
[0066] Example 2 In this embodiment, a composite current collector having a thickness of 8 micrometers is provided, which includes a polymer-based film PET having a thickness of 6 micrometers and an aluminum plating layer symmetrically provided on both sides of the polymer-based film, and the aluminum plating layer on one side has a thickness of 1 micrometer. The manufacturing process is specifically as follows:
[0067] (1) A polymer-based film PET with a thickness of 6 micrometers and a high-purity aluminum ingot with a purity of 99.9% were selected.
[0068] (2) The polymer-based film and a high-purity aluminum ingot were each placed in a vacuum deposition apparatus.
[0069] (3) The high-purity aluminum ingot is plated with aluminum on the upper and lower surfaces of the polymer-based film by a vacuum deposition device to obtain an aluminum plating layer. The unwinding tension of the polymer-based film is 8N. The aluminum plating layer on one side needs to be deposited twice. The first deposition is to obtain a first sublayer, the aluminum particles of which have a diameter of 20 nm, and the second deposition is to obtain a second sublayer, the aluminum particles of which have a diameter of 85 nm. The process parameters for the deposition process are a vacuum degree of 5×10 -2 The deposition temperature was 700°C for the first evaporation and 620°C for the second evaporation.
[0070] (4) After the deposition was completed, a winding operation was carried out with a winding tension of 6 N to obtain the composite current collector of this example.
[0071] Example 3 In this embodiment, a composite current collector having a thickness of 8 micrometers is provided, which includes a polymer-based film PET having a thickness of 6 micrometers and an aluminum plating layer symmetrically provided on both sides of the polymer-based film, and the aluminum plating layer on one side has a thickness of 1 micrometer. The manufacturing process is specifically as follows:
[0072] (1) A polymer-based film PET with a thickness of 6 micrometers and a high-purity aluminum ingot with a purity of 99.9% were selected.
[0073] (2) The polymer-based film and a high-purity aluminum ingot were each placed in a vacuum deposition apparatus.
[0074] (3) The high-purity aluminum ingot is plated with aluminum on the upper and lower surfaces of the polymer-based film by a vacuum deposition device to obtain an aluminum plating layer. The unwinding tension of the polymer-based film is 8N. The aluminum plating layer on one side needs to be evaporated 16 times. Among them, the first 15 evaporations are performed to obtain 15 first sublayers, and the aluminum particles in each first sublayer have a diameter of 10 nm. The 16th evaporation is performed to obtain a second sublayer, and the aluminum particles in the second sublayer have a diameter of 100 nm. The process parameters in the evaporation process are a vacuum degree of 5×10 -2 The evaporation temperature for the first 15 times was 740°C, and the evaporation temperature for the 16th time was 650°C.
[0075] (4) After the deposition was completed, a winding operation was carried out with a winding tension of 6 N to obtain the composite current collector of this example.
[0076] Comparative Example 1 Comparative Example 1 provides a conventional aluminum foil positive electrode current collector with a manufacturing thickness of 8 micrometers. The manufacturing process is specifically as follows:
[0077] (1) The electrolytic aluminum melt was fed into a smelting furnace, and 30% of the total weight of the electrolytic aluminum melt was added with an aluminum ingot, and the melt temperature was controlled to 770°C. The mass percentage of each element in the melt was adjusted to Si: 0.15%, Fe: 0.48%, Cu: 0.13%, Mn: 1.3%, Ti: 0.03%, and the balance was Al. The smelt was refined by spraying a refining agent onto it with pure nitrogen gas or pure argon gas, and the mixture was thoroughly and uniformly stirred for 9 minutes. After that, it was left to stand for 20 minutes, and the dross on the surface of the aluminum liquid was removed, and the mixture was put into a static furnace, and the temperature in the static furnace was controlled to 755°C. The aluminum liquid in the static furnace was fed into a trough, and aluminum titanium boron thread was added in the opposite direction to refine the crystal grains. After that, the aluminum liquid was degassed in a degassing box with pure nitrogen gas or pure argon gas. After degassing, the aluminum liquid was filtered and purified using a ceramic foam filter sheet. The purified aluminum liquid was fed into a rolling mill and rolled into a billet with a thickness of 4.0 mm.
[0078] (2) The billet obtained in step (1) is cold-rolled to a thickness of 4.0 mm, and then subjected to homogenization annealing, the homogenization annealing temperature is 470° C., and the annealing time is 25 hours.
[0079] (3) The homogenized annealed billet is cold rolled to a thickness of 0.5 mm, and then subjected to recrystallization annealing, the temperature of the recrystallization annealing is 300° C., and the annealing time is 15 hours.
[0080] (4) The recrystallization-annealed billet was rolled into an 8 micrometer aluminum foil to obtain the current collector of Comparative Example 1.
[0081] Comparative Example 2 Comparative Example 2 provides a composite current collector having a thickness of 8 micrometers, which includes a polymer-based film PET having a thickness of 6 micrometers and an aluminum plating layer symmetrically provided on both sides of the polymer-based film, and the aluminum plating layer on one side has a thickness of 1 micrometer. The manufacturing process is specifically as follows:
[0082] (1) A polymer-based film PET with a thickness of 6 micrometers and a high-purity aluminum ingot with a purity of 99.9% were selected.
[0083] (2) The polymer-based film and a high-purity aluminum ingot were each placed in a vacuum deposition apparatus.
[0084] (3) The high-purity aluminum ingot was plated with aluminum on the top and bottom surfaces of the polymer-based film using a vacuum deposition device to obtain an aluminum plating layer. The unwinding tension of the polymer-based film was 8N. The aluminum plating layer on one side needed to be evaporated 16 times. The grain size of the aluminum particles in each layer was 20 nm. The process parameters for the evaporation process were evaporation temperature 700°C, vacuum degree 5×10 -2 The pressure was 50 Pa and the deposition speed was 50 m / min.
[0085] (4) After the deposition was completed, a winding operation was carried out with a winding tension of 6 N to obtain a composite current collector of Comparative Example 2.
[0086] Comparative Example 3 Comparative Example 3 provides a composite current collector with a thickness of 8 micrometers, which includes a polymer-based film PP with a thickness of 6 micrometers and an aluminum plating layer symmetrically provided on both sides of the polymer-based film, and the aluminum plating layer on one side has a thickness of 1 micrometer. The manufacturing process is specifically as follows:
[0087] (1) A polymer-based film PET with a thickness of 6 micrometers and a high-purity aluminum ingot with a purity of 99.9% were selected.
[0088] (2) The polymer-based film and a high-purity aluminum ingot were each placed in a vacuum deposition apparatus.
[0089] (3) The high-purity aluminum ingot was plated with aluminum on the top and bottom surfaces of the polymer-based film by a vacuum deposition device to obtain an aluminum plating layer. The unwinding tension of the polymer-based film was 8N. The aluminum plating layer on one side needed to be deposited 16 times. The grain size of the aluminum particles in each layer was 85nm. The process parameters for the deposition process were evaporation temperature 620℃, vacuum degree 5×10 -2 The pressure was 50 Pa and the deposition speed was 50 m / min.
[0090] (4) After the deposition was completed, a winding operation was carried out with a winding tension of 6 N to obtain a composite current collector of Comparative Example 3.
[0091] Comparative Example 4 Comparative Example 4 provides a composite current collector having a thickness of 8 micrometers, which includes a polymer-based film PET having a thickness of 6 micrometers and an aluminum plating layer symmetrically provided on both sides of the polymer-based film, and the aluminum plating layer on one side has a thickness of 1 micrometer. The manufacturing process is specifically as follows:
[0092] (1) A polymer-based film PET with a thickness of 6 micrometers and a high-purity aluminum ingot with a purity of 99.9% were selected.
[0093] (2) The polymer-based film and a high-purity aluminum ingot were each placed in a vacuum deposition apparatus.
[0094] (3) The high-purity aluminum ingot is plated with aluminum on the upper and lower surfaces of the polymer-based film by a vacuum deposition device to obtain an aluminum plating layer. The unwinding tension of the polymer-based film is 8N. The aluminum plating layer on one side needs to be evaporated 16 times. The first 15 evaporations are used to obtain 15 first sublayers, each of which has an aluminum particle diameter of 85nm, and the 16th evaporation is used to obtain a second sublayer, each of which has an aluminum particle diameter of 20nm. The process parameters for the evaporation process are a vacuum degree of 5×10 -2The evaporation temperature for the first 15 runs was 620°C, and the evaporation temperature for the 16th run was 700°C.
[0095] (4) After the deposition was completed, a winding operation was carried out with a winding tension of 6 N to obtain a composite current collector of Comparative Example 4.
[0096] Comparative Example 5 Comparative Example 5 provides a composite current collector having a thickness of 8 micrometers, which includes a polymer-based film PET having a thickness of 6 micrometers and an aluminum plating layer symmetrically provided on both sides of the polymer-based film, and the thickness of the aluminum plating layer on one side is 1 micrometer. The manufacturing process is specifically as follows:
[0097] (1) A polymer-based film PET with a thickness of 6 micrometers and a high-purity aluminum ingot with a purity of 99.9% were selected.
[0098] (2) The polymer-based film and a high-purity aluminum ingot were each placed in a vacuum deposition apparatus.
[0099] (3) The high-purity aluminum ingot is plated with aluminum on the upper and lower surfaces of the polymer-based film by a vacuum deposition device to obtain an aluminum plating layer. The unwinding tension of the polymer-based film is 8N. The aluminum plating layer on one side needs to be evaporated 16 times. Among them, the first 15 evaporations are performed to obtain 15 first sublayers, and the aluminum particles in each first sublayer have a diameter of 50nm. The 16th evaporation is performed to obtain a second sublayer, and the aluminum particles in the second sublayer have a diameter of 85nm. The process parameters in the evaporation process are a vacuum degree of 5×10 -2 The evaporation temperature for the first 15 runs was 720°C, and the evaporation temperature for the 16th run was 620°C.
[0100] (4) After the deposition was completed, a winding operation was carried out with a winding tension of 6 N to obtain a composite current collector of Comparative Example 5.
[0101] Comparative Example 6 Comparative Example 6 provides a composite current collector having a thickness of 8 micrometers, which includes a polymer-based film PET having a thickness of 6 micrometers and an aluminum plating layer symmetrically provided on both sides of the polymer-based film, and the aluminum plating layer on one side has a thickness of 1 micrometer. The manufacturing process is specifically as follows:
[0102] (1) A polymer-based film PET with a thickness of 6 micrometers and a high-purity aluminum ingot with a purity of 99.9% were selected.
[0103] (2) The polymer-based film and a high-purity aluminum ingot were each placed in a vacuum deposition apparatus.
[0104] (3) The high-purity aluminum ingot is plated with aluminum on the upper and lower surfaces of the polymer-based film by a vacuum deposition device to obtain an aluminum plating layer. The unwinding tension of the polymer-based film is 8N. The aluminum plating layer on one side needs to be evaporated 16 times. The first 15 evaporations are used to obtain 15 first sublayers, each of which has an aluminum particle diameter of 20nm, and the 16th evaporation is used to obtain a second sublayer, each of which has an aluminum particle diameter of 120nm. The process parameters for the evaporation process are a vacuum degree of 5×10 -2 The evaporation temperature for the first 15 runs was 700°C, and the evaporation temperature for the 16th run was 600°C.
[0105] (4) After the deposition was completed, a winding operation was carried out with a winding tension of 6 N to obtain a composite current collector of Comparative Example 6.
[0106] The performance of the composite current collectors obtained in the above examples and comparative examples was tested, and the test results shown in Table 1 below were obtained. Among them, the conductivity of the aluminum plating layer on one side was tested using a four-point probe tester, and the surface energy of the aluminum plating layer was tested using a dyne pen. The composite current collector and the positive electrode active material were combined to obtain a positive electrode piece, which was then assembled into a lithium battery together with a negative electrode piece, an electrolyte, and a separator, and the internal resistance of the lithium battery (capacity 50 Ah) and the capacity retention rate after 1000 cycles were measured. The results of the internal resistance of the lithium batteries manufactured using the current collectors of Example 1 and Comparative Example 1 are shown in FIG. 2.
[0107] [Table 1]
[0108] As can be seen from the above experimental data, by using the composite current collector in the examples, it is possible to improve the surface energy while maintaining the electrical conductivity, and further to improve the capacity retention rate of the battery and reduce the internal resistance.
[0109] The technical features of the above embodiments can be combined in any manner. For the sake of simplicity, all possible combinations of the technical features in the above embodiments are not described, but as long as there is no contradiction in the combination of these technical features, they should all be considered within the scope of the present specification.
[0110] It should be understood that the above examples are merely illustrative of some embodiments of the present invention, and are intended to provide a specific and detailed understanding of the technical solution of the present invention, but do not limit the scope of the present invention. It should be noted that a person skilled in the art can make some modifications and improvements without departing from the concept of the present invention, and all of these fall within the scope of protection of the present invention. It should be understood that any technical solution obtained by a person skilled in the art through logical analysis, estimation or limited testing based on the technical solution of the present invention falls within the scope of the claims of the present invention. Therefore, the scope of protection of the present invention is subject to the claims, and the specification and drawings are used to interpret the contents described in the claims.
[0111] (Additional Note) (Appendix 1) The present invention includes a polymer-based film and an aluminum plating layer provided on both surfaces of the polymer-based film, The aluminum plating layer includes a first sublayer and a second sublayer, the first sublayer is closer to the polymer-based film than the second sublayer, the aluminum particles in the first sublayer have a particle size of 10 nm to 30 nm, and the aluminum particles in the second sublayer have a particle size of 80 nm to 100 nm. A composite current collector comprising:
[0112] (Appendix 2) The thickness of each of the aluminum plating layers is independently 0.3 μm to 3 μm. 2. The composite current collector according to claim 1,
[0113] (Appendix 3) The first sublayer is a plurality of first sublayers, and the plurality of first sublayers are sequentially stacked and arranged between the polymer-based film and the second sublayer. 2. The composite current collector according to claim 1,
[0114] (Appendix 4) The number of first sublayers is 19 or less. 4. The composite current collector according to claim 3,
[0115] (Appendix 5) The thickness of the polymer-based membrane is 1 μm to 25 μm. 5. The composite current collector according to claim 1, wherein the composite current collector is a
[0116] (Appendix 6) The polymer-based film is at least one selected from polyethylene, polypropylene, polymethylpentene, and polyethylene terephthalate; 5. The composite current collector according to claim 1, wherein the composite current collector is a
[0117] (Appendix 7) A method for producing a composite current collector, comprising the steps of forming an aluminum plating layer on both sides of a polymer-based film to produce a composite current collector, The aluminum plating layer includes a first sublayer and a second sublayer, the first sublayer is closer to the polymer-based film than the second sublayer, the aluminum particles in the first sublayer have a particle size of 10 nm to 30 nm, and the aluminum particles in the second sublayer have a particle size of 80 nm to 100 nm. A method for producing a composite current collector comprising the steps of:
[0118] (Appendix 8) The aluminum plating layer is formed by vacuum deposition or magnetron sputtering. 8. A method for producing a composite current collector according to claim 7,
[0119] (Appendix 9) In the process of forming the aluminum plating layer, the process parameters are: evaporation temperature is 600° C. or more, vacuum degree is less than 0.01 Pa, plating speed is more than 10 m / min, and the evaporation temperature for forming the first sub-layer is higher than the evaporation temperature for forming the second sub-layer. 9. A method for producing a composite current collector according to claim 8,
[0120] (Appendix 10) The evaporation temperature for forming the first sublayer is 700°C to 750°C, and the evaporation temperature for forming the second sublayer is 600°C to 700°C. 10. The method for producing a composite current collector according to claim 9,
[0121] (Appendix 11) A current collector comprising the composite current collector according to any one of appendices 1 to 6 or the composite current collector manufactured by the method for manufacturing a composite current collector according to any one of appendices 7 to 10, and an active material applied to both sides of the current collector. An electrode piece characterized by:
[0122] (Appendix 12) Including the electrode piece according to claim 11, A secondary battery comprising:
Claims
1. The present invention includes a polymer-based film and an aluminum plating layer provided on both surfaces of the polymer-based film, The aluminum plating layer includes a first sublayer and a second sublayer, the first sublayer is closer to the polymer-based film than the second sublayer, the aluminum particles in the first sublayer have a particle size of 10 nm to 30 nm, and the aluminum particles in the second sublayer have a particle size of 80 nm to 100 nm. A composite current collector comprising:
2. The thickness of each of the aluminum plating layers is independently 0.3 μm to 3 μm; 2. The composite current collector according to claim 1 .
3. The first sublayer is a plurality of first sublayers, and the plurality of first sublayers are sequentially stacked and arranged between the polymer-based film and the second sublayer.
2. The composite current collector according to claim 1 .
4. The number of the first sublayers is 19 or less.
4. The composite current collector according to claim 3.
5. The thickness of the polymer-based membrane is between 1 μm and 25 μm; 5. The composite current collector according to claim 1, wherein the composite current collector is a metal oxide.
6. The polymer base film is at least one selected from polyethylene, polypropylene, polymethylpentene and polyethylene terephthalate; 5. The composite current collector according to claim 1, wherein the composite current collector is a metal oxide.
7. A method for producing a composite current collector, comprising the steps of forming an aluminum plating layer on both sides of a polymer-based film to produce a composite current collector, The aluminum plating layer includes a first sublayer and a second sublayer, the first sublayer is closer to the polymer-based film than the second sublayer, the aluminum particles in the first sublayer have a particle size of 10 nm to 30 nm, and the aluminum particles in the second sublayer have a particle size of 80 nm to 100 nm. A method for producing a composite current collector comprising the steps of:
8. The aluminum plating layer is formed by vacuum deposition or magnetron sputtering. The method for producing a composite current collector according to claim 7 .
9. In the process of forming the aluminum plating layer, the process parameters are: evaporation temperature is 600° C. or more, vacuum degree is less than 0.01 Pa, plating speed is more than 10 m / min, and the evaporation temperature for forming the first sublayer is higher than the evaporation temperature for forming the second sublayer. The method for producing a composite current collector according to claim 8 .
10. The evaporation temperature for forming the first sublayer is 700°C to 750°C, and the evaporation temperature for forming the second sublayer is 600°C to 700°C. The method for producing a composite current collector according to claim 9 .
11. A current collector comprising the composite current collector according to any one of claims 1 to 6 or a composite current collector manufactured by the method for manufacturing a composite current collector according to any one of claims 7 to 10, and an active material applied to both sides of the current collector. An electrode piece characterized by:
12. The electrode strip according to claim 11, A secondary battery comprising:
Citation Information
Patent Citations
Current collector for lithium ion battery and preparation method of current collector
CN105762365A
Coating process for lithium battery current collectors
CN108531876A